HUBUNGAN KECERDASAN VISUAL-SPASIAL DENGAN HASIL BELAJAR GAMBAR INTERIOR EKSTERIOR BANGUNAN GEDUNG SISWA KELAS XII JURUSAN TGB DI SMK NEGERI 1 BUKITTINGGI - Muhammad Hidayat Mulfi; Dr. Fahmi Rizal, M.Pd, M.T (CIVED, 2019)
Abstract— This study aims to find out the relationship between Visual-Spatial Intelligence and learning outcomes. The type of this research is descriptive correlation. This research was carried out in the Department of Building Drawing Engineering at SMK Negeri 1 Bukittinggi. Informants / respondents in this study were students of class XII majoring in TGB. Data collection techniques in this study used the Test method. While the Sampling Technique used is Total Sampling. The Total Sampling technique is a data collection technique where the sampling technique is the same as the population. The reason for taking total sampling is because the population is less than 100, so the entire population is all research. In this study there were 48 informants. The results of this study indicate that there is a significant relationship between Visual-Spatial Intelligence and Learning Outcomes of Interior Buildings and Exterior Buildings. Keywords: Visual-Spatial Intelligence, Learning Outcomes